Strategic Management for The Success of Legislative Candidates in the 2024 Election Campaign Period - Muhammad Aras Prabowo; Shabrina Munthazah; Mohammad Zuhdi; Fitriah Ulfah; Taufik Hidayadi; Mohd Rushdan Yasoa; Fitria Auldry Desiana (Mandalika Institute, 2025)
This study aims to analyse the management and winning strategies used by legislative candidates during the general election campaign. Elections include a democratic process, in which legislative candidates compete to get votes from the public. Success in winning an election is highly dependent on effective campaign management and strategy. Using a case study approach, this research compares two legislative candidates with different backgrounds in terms of political parties, electoral districts, and personal characteristics. The results showed differences in the management and winning strategies used by the two candidates. Factors such as financial resources, a solid campaign team, the establishment of a support network, and the utilisation of social and conventional media were key elements that influenced the effectiveness of the campaign. This research provides insights into best practices in the management and winning strategies of legislative candidates, and highlights the importance of adapting to changes in the political environment and new trends in campaigning.